Analysis of the Impact of Economic Digitalization on Economic Growth on the Island of Sumatra - Ismail Pulungan Ismail; Lalu Abu Gunawan; Fery Maulana Malik; Muhammad Ariful Maarif (Journal of Islamic Economics Perspectives, 2025)
This study examines the impact of economic digitalization on economic growth in Sumatra from 2013 to 2023. As economic digitalization plays a significant role in shaping growth trajectories, this research focuses on analyzing its effect on various economic indicators, including government spending and production. Using panel data from 49 districts/cities on the island of Sumatra, the study employs a dynamic panel data model with the Generalized Method of Moments (GMM) approach, particularly the Arellano-Bond estimator, to estimate the long-term and short-term impacts. The results indicate that economic digitalization significantly influences economic growth in Sumatra, with digitalization showing positive effects both in the short and long term. Furthermore, government spending is found to have a notable impact on the region’s digitalization efforts, whereas production does not exhibit a significant effect. The study concludes that fostering digitalization through targeted policies, investments in digital infrastructure, and increased government expenditure can drive sustainable economic growth in Sumatra. The findings suggest that enhancing digitalization initiatives and inter-regional cooperation could maximize economic potential and ensure equitable growth across the island.